Internalizing and Externalizing Symptoms in Adolescents With and Without Experiences of Physical Parental Violence, a Latent Profile Analysis on Violence Resilience - Aksoy, Dilan; Favre, Céline A.; Janousch, Clarissa; Ertanir, Beyhan (Frontiers in Psychology, 2022)
Questionnaire data from a cross-sectional study on social resilience in adolescence, with a sample of N= 1,974 Swiss seventh grade high school students ages 12 – 14 (M = 11.76; SD = .65) was used to identify and compare violence resilience profiles. Person-centered latent profile analysis (LPA) was applied and allowed for the grouping of adolescents into profiles of internalizing (depression/anxiety, dissociation) and externalizing symptoms (peer aggression, peer victimization, classroom disruption) and differentiation of adolescents with (n= 403) and without (n = 1,571) physical parental violence experiences. Subsequently, a multinomial logistic regression analysis was conducted to further investigate the sociodemographic predictors of violence resilience profiles. With LPA, we identified four distinct profiles for both adolescent groups (with and without parental physical violence experiences). The results showed three particularly burdened profiles of adolescents, one with higher externalizing and one with higher internalizing symptoms, which did not occur simultaneously to the same extent. Furthermore, the third profile contained adolescents with both elevated internalizing and externalizing symptoms, the comorbid profile. The fourth profile consisted of the majority of adolescents, who exhibited little or no internalizing and externalizing symptoms, the so-called no/low symptomatic profile. A differentiated view of the symptoms can create added value regarding the understanding of violence resilience. Moreover, in the multinomial logistic regression, significant associations were found between the profiles and adolescents’ gender in the group of adolescents with parental physical violence experiences, but none were found in relation to sociocultural status and migration background.